Acute Toxicity of Ethanol Extract of Curcuma zedoaria Rosc (Zingiberaceae) Rhizomes on Brine Shrimp Larvae and Zebrafish Embryos - Syahbirin, Gustini; Aditianingrum, Kurnia Alysia; Mohamad, Kusdiantoro (Universitas Airlangga, 2024)
Curcuma zedoaria Rosc (Zingiberaceae), known as white turmeric or temu putih, is commonly used as traditional medicine in Indonesia. The toxicity of this herb needs to be studied to improve its application. This study aimed to evaluate the toxicity of the crude ethanol extract of temu putih rhizome against brine shrimp (Artemia salina) larvae and zebrafish (Danio rerio) embryos and to analyze the potential active compounds contained in the extract. The crude ethanol extract showed a 50% lethal concentration value (LC50) at 588 ppm against brine shrimp larvae and 224 ppm against zebrafish embryos. Based on the gas chromatography-mass spectrometry analysis, the suspected active compounds that play a role in the toxicity were epicurzerenone, curzerene, and curzerenone, while 2,4,6-trimethylacetophenone was the predominant compound.